Relationship of Knowledge and Interest with Participation of Family Planning (KB) Postpartum in Trimester III Pregnant Women at Ummu Kultsum Sanipah Clinic 2023 - Nur Jannah H; Ni Nyoman Murti; Endah Wijayanti (Formosa Journal of Science and Technology, 2023)
The number of post-natal family planning users in the Sanipah area in 2021 is 82 PUS (80%) out of 1,010 target PUS, in 2022 there will be 89 couples of childbearing age (91%) from 1,118 target PUS. The aim of the research was to determine the relationship between knowledge and interest and postpartum family planning participation in third trimester pregnant women. This type of research is analytical observation using a cross sectional design. There is a relationship between knowledge and postnatal family planning (KB) participation (p value: 0.005 < α: 0.05). There is a relationship between knowledge and interest with postnatal family planning participation. It is hoped that health workers will always be active in maximizing postnatal family planning participation by providing counseling.